Investigating Possible Effects from a One-Year Coach-Education Program - Frode Moen; Maja Olsen; John Anders Bjørkøy (MDPI AG, 2020)
The main purpose of the current study was to examine possible effects from a coach education program over one year, in which each coach was supervised by a mentor who facilitated their learning based on coach-centered values. The current study was designed as an experiment with a control group, where the coaches in the experiment group received mentoring by a mentor over one year, whereas the coaches in the control group did not. Ninety-four coaches completed the study over one year from a variety of sports (n > 30), where cross-country skiing, soccer, biathlon, handball and swimming were the most represented sports. Among the coaches in the sample, 87% were coaches for athletes who competed or had ambitions to compete at an international level. The results from self-reported questionnaires at the pre-test and post-test show that the coach education program had a significant effect on the bond dimension in the coach-athlete working alliances and the coaches' perceived coach performances. The analysis did not find any effects from the coach education program on the goal and task dimension in the coach-athlete working alliances. The findings are discussed in terms of applied implications and possible future research.